2008
DOI: 10.1016/j.esp.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Participation and performance in international business meetings

Abstract: With the continuing globalisation of markets and internationalisation of trade, professionals from a wide range of organisations, from large multinational corporations to small to medium size enterprises, are increasingly coming together to do business in the international workplace, particularly in meetings. Such international events usually bring together people from different linguistic and socio-cultural backgrounds with the result that a common language of communication is frequently adopted. More often t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 19 publications
2
59
0
1
Order By: Relevance
“…The use of a corporate language may exclude non-native staff lacking adequate proficiency from communication processes, and, conversely, put considerable power into the hands of those individuals or units that do possess the required language skills (Welch et al 2005). In her analysis of international business meetings, Rogerson-Revell (2008) showed that the use of English as a Lingua Franca (ELF) may lead to feelings of frustration in meetings and that a considerable proportion of non-native participants were inactive in ELF meetings. Participants tend to have negative perceptions about their own contributions (RogersonRevell 2008).…”
mentioning
confidence: 96%
“…The use of a corporate language may exclude non-native staff lacking adequate proficiency from communication processes, and, conversely, put considerable power into the hands of those individuals or units that do possess the required language skills (Welch et al 2005). In her analysis of international business meetings, Rogerson-Revell (2008) showed that the use of English as a Lingua Franca (ELF) may lead to feelings of frustration in meetings and that a considerable proportion of non-native participants were inactive in ELF meetings. Participants tend to have negative perceptions about their own contributions (RogersonRevell 2008).…”
mentioning
confidence: 96%
“…Indeed, much BELF research, as with ELF research more generally, has focused on the phenomenon of accommodation and has demonstrated that BELF speakers accommodate in various ways in order to ensure understanding and communicative efficiency (Connor 1999;Pitzl 2005;Rogerson-Revell 2008;Ehrenreich 2009;Koester 2010 Kankaanranta & Louhiala-Salminen 2007). But regardless of their specific focus, the findings of BELF studies demonstrate that intercultural communication skills rather than NS English correctness are key in BELF contexts, and BELF researchers therefore tend to conclude that communication and accommodation, rather than mastery of NS English forms, should be the focus of business English instruction.…”
Section: Business Elf Settingsmentioning
confidence: 99%
“…Her work is an excellent example of the three way relationship that can exist between consultancy work, sound research, and teaching or training materials. Rogerson-Revell (2007), for instance, investigates the strategies used by the participants in business meetings in EIL at a European business organization, while Rogerson-Revell (2008) looks specifically at the difference between the strategies used by native speakers and non-native speakers of English in business meetings, and Rogerson-Revell (2010) at the accommodation strategies that occur in business meetings in EIL and how these can be incorporated into training materials (see also Chapter 7).…”
Section: Quote 41 the Importance Of Foreign Language Skillsmentioning
confidence: 99%